Estimates and physicochemical properties of food waste in Bandar Baru Bangi - Leow, Kim Teck; Aminah Abdullah,; Mushrifah Idris, (Universiti Kebangsaan Malaysia, 2010)
Estimating the quantity and physicochemical characterization of food waste is necessary to optimize composting process. A survey was conducted to estimate the amount of food waste generated by commercial (n=10) and household (n=50) sectors in Bandar Baru Bangi. The presence of cooked rice residue, meat based residue, fish based residue, vegetable and fruit residue and whether the food waste was in wet condition were also examined. Physicochemical characteristics of the food waste was also analysed. About 11.41 MT of food waste was generated daily in Bandar Baru Bangi. From the total, household sector contributed 67.3% whereas commercial sector contributed another 32.7%. Compared to household sector, food waste in wet condition was found more frequently (p<0.05) in the commercial sector. Rice residue was the most frequent food waste component of household and the commercial sector. Physicochemical analysis showed that pH value, ash, organic matter, organic carbon, nitrogen and crude fat contents as well as C/N ratio were found significantly different (p<0.05) among food waste generated on different days. Food waste was acidic (pH 4.82-5.17), contained high moisture (65.9 – 69.5%) and crude fat content (13.1 – 20.2%) but low in nitrogen content (0.63 – 0.85%). Nevertheless, the C/N ratio was still within an appropriate range (20-25) for effective composting. Hence, if composting process is introduced, the food waste has the potential to be converted into compost.